Successful Management of Rhinocerebral Mucormycosis in a Child with Uncontrolled Diabetes Mellitus and Recent Blindness: A Case Report - H Daneste; N Ghadimi; M Mardani; SH Maleki; MH Anbardar; S Sharifzadeh (Islamic Azad University, 2022)
Background and Aim: Mucormycosis is an aggressive and life-threating fungal infection that affects patients with uncontrolled diabetes mellitus (DM) or compromised immune system. The most common symptom of rhinocerebral mucormycosis is sinusitis, and if the infection spreads beyond the sinus, more severe symptoms such as blindness, seizure, and death may occur. Case Presentation: We describe a case of rhinocerebral mucormycosis successfully treated in an 11-year-old boy with uncontrolled DM and neglected sinusitis with sudden blindness. Conclusion:  Patients with poorly controlled or insulin-dependent DM who experience periods of ketoacidosis are more likely to develop mucormycosis. Therefore, correct diagnosis and timely referral of patients greatly affect the prognosis of the disease and the treatment process.